2007
DOI: 10.1136/bjo.2006.098525
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation for ocular disease: a review of the first 233 cases from the UK user group

Abstract: Although the outcome criteria used in this study were stringent, and the follow-up duration was short, the results of AMT by this user group were generally less favourable than those of previously reported case series. Controlled clinical trials would improve the quality of evidence for use of amniotic membrane in ocular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 35 publications
0
16
0
2
Order By: Relevance
“…For the control group, the results were better than expected probably because the corneal lesions were too superficial in our model. However, this method was previously used for treatment of bullous keratophathy with good results (18)(19) . Clinical evaluation between Groups 1 and 2 showed no statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…For the control group, the results were better than expected probably because the corneal lesions were too superficial in our model. However, this method was previously used for treatment of bullous keratophathy with good results (18)(19) . Clinical evaluation between Groups 1 and 2 showed no statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies have reported that AMT can be used to treat partial LSCD on its own or to treat total LSCD by limbal allografting.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AM is usually reserved for cases where primary conservative measures (ocular lubricants, therapeutic contact lenses, and autologous serum [if available]) have failed, and/or when there has been loss of Bowman's layer, when AM is used as a BM substrate enabling corneal epithelial cell migration and closure of the epithelial defect. In a review of the first 233 cases of the UK users group (Saw et al 2007), the most common surgical technique for PED was the use of an AM sutured BM side up within the confines of the defect and a second piece of membrane secured BM side up as an overlay patch (Fig. 4).…”
Section: Persistent Corneal Epithelial Defectsmentioning
confidence: 99%